Systematic Review and Network Meta-Analysis: Comparative Efficacy and Safety of Biosimilars, Biologics and JAK1 Inhibitors for Active Crohn Disease - Wu, Guozhi; Yang, Yuan; Liu, Min; Wang, Yuping; Guo, Qinghong (Frontiers in Pharmacology, 2021)
Background: Crohn disease (CD) is a chronic inflammatory disease affecting life quality of people. There are several drugs available for the treatment of CD, but their relative efficacy is unknown due to lack of high-quality head-to-head randomized controlled trials. Aim: To perform a mixed comparison of efficacy and safety of biosimilar, biologics and JAK1 inhibitors for CD. Methods: We searched PubMed, Web of Science, Embase and the Cochrane library for randomized-controlled trials (RCTs) with the deadline of Dec 28, 2020. Only RCTs on assessing the efficacy or safety of biosimilar, biologics and JAK1 inhibitors with placebo or another active agent for CD were included in the comparative analysis. Efficacy outcomes were reported as induction of remission, maintenance of remission and steroid-free remission; and safety outcomes were serious adverse events (AEs) and infections. Bayesian method was utilized to compare each treatment. The registration number is CRD42020187807. Results: 28 studies and 29 RCTs totally were identified in our systematic review. The network meta-analysis demonstrated that infliximab and adalimumab are superior to certolizumab pegol (OR 2.44, 95%CI 1.35-4.97; OR 2.96, 95%CI 1.57-5.40, respectively) and tofacitinib (OR 2.55, 95%CI 1.27-5.97; OR 3.10, 95%CI 1.47-6.52, respectively), and revealed the superiority of CT-P13 compared with placebo (OR 2.90, 95%CI 1.31-7.59) for induction of remission. Infliximab (OR 7.49, 95%CI 1.85-34.77), adalimumab (OR 10.76, 95%CI 2.61-52.35), certolizumab pegol (OR 4.41, 95%CI 1.10-21.08), vedolizumab (OR 4.99, 95%CI 1.19-25.54) and CT-P13 (OR 10.93, 95%CI 2.10-64.37) were superior to filgotinib for maintenance of remission. Moreover, infliximab (OR 3.80, 95%CI 1.49-10.23), adalimumab (OR 4.86, 95%CI 1.43-16.95), vedolizumab (OR 2.48, 95%CI 1.21-6.52) and CT-P13 (OR 5.15, 95%CI 1.05-27.58) showed the superiority over placebo for steroid-free remission. Among all of treatments, adalimumab ranked highest for induction of remission, CT-P13 ranked highest for maintenance of remission and steroid-free remission. Conclusions: CT-P13 was more efficacious than numerous biological agents and JAK1 inhibitors and deserved to be recommended for treatment of CD. Further head-to-head RCTs are warranted to compare these drugs.